PENGARUH HEXAGON’S FRAUD TERHADAP FRAUDULENT FINANCIAL STATEMENT: PERAN AUDIT COMMITTEE SEBAGAI VARIABEL MODERASI - Safitri, Alfika Nurul; Karmudiandri, Arwina (E-Jurnal Akuntansi TSM, 2026)
The purpose of this study is to gather empirical evidence on the influence of external pressure, change in auditor, nature of industry, CEO duality, change in director, political connection, and financial stability in relation to fraudulent financial statement. In addition, this study aims to examine the relationship between external pressure, change in auditor, nature of industry, CEO duality, change in director, political connection through the audit committee on fraudulent financial statement. This research utilizes 119 manufacturing companies listed on the Indonesia Stock Exchange over the past three years (2021-2023). The sample was selected using the purposive sampling method, and the data were analyzed using multiple linear regression analysis. The results of this study indicate that the variable nature of industry significantly affect fraudulent financial statement. Additionally, the audit committee is able to moderate the influence of nature of industry on fraudulent financial statement.